Socialization of Microcontroller use in Medical Support Equipment for Indonesian Electromedical Students - Jaya, Indra; Muhammad Nawawi (CV. Media Digital Publikasi Indonesia, 2024)
Socialization of Microcontroller Use in Medical Support Equipment for Electromedical Students undertaken by the Muhammadiyah Aceh School of Health Sciences. The project aims to enhance the understanding and skills of students in using microcontrollers for medical devices, thereby improving healthcare support in the community. Through a series of webinars, the initiative addressed critical issues related to the utilization of microcontrollers in the design and maintenance of medical equipment. The target audience included electromedical students from various campuses in Sumatra, emphasizing the integration of theoretical knowledge with practical applications. The results indicated significant improvements in participants' knowledge and skills, highlighting the importance of such programs in fostering technological advancements in the healthcare sector. This initiative not only contributes to the educational development of students but also plays a crucial role in enhancing healthcare service delivery.